2008
DOI: 10.1016/s0022-5347(08)61385-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression After Vaginal Distension of Different Durations in Virgin Sprague Dawley Rats

Abstract: Purpose-To investigate the effect of duration of vaginal distention (VD) on the differential expression of stem cell homing and tissue repair cytokines and cytokine receptors in order to identify factors most important for recovery from injury.Methods-Twenty 10-week-old virgin Sprague-Dawley rats were divided into 4 groups: 1-hour VD, 4-hour VD, 6-hour VD, and anesthetized shams. Vagina, bladder, urethra and rectum were harvested immediately after VD and Real-Time PCR was used to determine relative expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Recent studies have shown that SDF-1 levels are related to the degree of hypoxia, such that hypoxic gradients in tissues directly correlate with SDF-1 gene expression (28). SDF-1 was significantly under-expressed immediately after VD in all tissues in SD animals (17;18); however, it only showed a significant difference in the urethra and vagina, but not rectum and bladder in Lewis rats immediately after VD compared to control rats, suggesting that Lewis rats might have a different pattern of hypoxia after VD, consistent with experiments studying ischemia after stroke (27). Delayed expression of SDF-1 after VD is a possibility and will be investigated in future experiments.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Recent studies have shown that SDF-1 levels are related to the degree of hypoxia, such that hypoxic gradients in tissues directly correlate with SDF-1 gene expression (28). SDF-1 was significantly under-expressed immediately after VD in all tissues in SD animals (17;18); however, it only showed a significant difference in the urethra and vagina, but not rectum and bladder in Lewis rats immediately after VD compared to control rats, suggesting that Lewis rats might have a different pattern of hypoxia after VD, consistent with experiments studying ischemia after stroke (27). Delayed expression of SDF-1 after VD is a possibility and will be investigated in future experiments.…”
Section: Discussionsupporting
confidence: 81%
“…MCP-3 quantification in Lewis rats following VD demonstrated overexpression patterns in the urethra and vagina similar to that of SD rats, suggesting similar gene expression profiles between the two strains (17;18). …”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations